DISCRIMINATION OF KEJAWEN BELIEVERS IN INDONESIA - Mahanani, Rosemary Rindiyaningtyas (Faculty of Law, Universitas Tanjungpura, 2024)
AbstractPopulation diversity can be found in Indonesia. The population is made up of several tribes, cultures, dialects, and faiths. There are many religions and beliefs that exist in Indonesia, one of which is Kejawen. Kejawen people have one view called Manunggaling Kawula Lan Gusti, which assumes that man's moral obligation is to achieve harmony with the ultimate power and the ultimate unity, that man surrenders himself as kawula to his God. Freedom to express religion is clearly stated as human rights on many national and international laws including the 1945 Constitution of the Republic of Indonesia. However, the discrimination is still felt by Kejawen believers in society. They are experiencing rejection, scorn, and judgment from others. Mostly, the reason is because they are seen as polytheistic based on the belief of the majority which is because of tolerance and knowledge of the Kejawen belief system. It is necessary to apply strict sanctions for people who discriminate against adherents of the Kejawen belief in order to create a safe and comfortable environment for all Indonesian people.AbstrakKeanekaragaman penduduk dapat ditemukan di Indonesia. Penduduk Indonesia terdiri dari berbagai suku, budaya, dialek, dan kepercayaan. Ada banyak agama dan aliran kepercayaan yang ada di Indonesia, salah satunya adalah Kejawen. Masyarakat Kejawen memiliki satu pandangan yang disebut Manunggaling Kawula Lan Gusti, yang mengasumsikan bahwa kewajiban moral manusia adalah untuk mencapai keselarasan dengan kekuatan tertinggi dan kesatuan tertinggi, bahwa manusia menyerahkan dirinya sebagai kawula kepada Tuhannya. Kebebasan untuk mengekspresikan agama secara jelas dinyatakan sebagai hak asasi manusia di banyak hukum nasional dan internasional termasuk Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Namun, diskriminasi masih dirasakan oleh para penghayat Kejawen di masyarakat. Mereka mengalami penolakan, cemoohan, dan penghakiman dari orang lain. Sebagian besar alasannya adalah karena mereka dianggap musyrik berdasarkan keyakinan mayoritas yang disebabkan oleh toleransi dan pengetahuan tentang sistem kepercayaan Kejawen. Perlu adanya penerapan sanksi yang tegas bagi masyarakat yang melakukan diskriminasi terhadap penganut kepercayaan Kejawen agar tercipta lingkungan yang aman dan nyaman bagi seluruh masyarakat Indonesia.